Effect of Energy-Restricted Diet in Combination with Calcium Supplement or Low-Fat Milk on Iron Status of Overweight or Obese Premenopausal Women - Shiva Faghih; Mehdi Hedayati (Shiraz University of Medical Sciences, 2015)
Background: Although it is assumed that calcium has beneficial effects on weight loss, the interaction of calcium and iron would be a major concern. We did this study to investigate the effects of calcium and low-fat milk on serum ferritin in overweight or obese premenopausal women. Methods: Sixty-four healthy overweight or obese premenopausal women recruited in Shahid Beheshti University of Medical Sciences clinics participated in this clinical trial. Participants were randomly allocated to one of the following dietary regimens for 8 weeks: 1) a control diet providing a 500 kcal/day deficit, with 500-600mg/day dietary calcium; 2) a calcium- supplemented diet identical to the control diet with 800mg/day calcium carbonate 3) a milk diet providing a 500kcal/day deficit and containing three servings of low fat milk. Serum ferritin and anthropometric indices were measured at baseline and after 8 weeks. Primary outcome measure was serum ferritin level. Results: Mean±SD of baseline values for age, body mass index (BMI), waist circumference (WC), and serum ferritin were 37.44±9.46 (year), 30.79±3.63 (kg/m2), 88.04±8.90 (cm), and 59.20±47.8 (μg/l), respectively. There were no significant differences in baseline age, BMI, WC, and serum ferritin among 3 groups. Mean values of serum ferritin reductions were 0.26±20.36, 14.59±17.07 and6.57±25.93 (μg/l) in control, calcium, and milk groups, respectively. Reduction in serum ferritin was only significant in the calcium group (P=0.003). Serum ferritin reductions were not significantly different among the 3 groups (P=0.260). Conclusion: An energy-restricted diet in combination with calcium supplement or low-fat milk does not induce any additional adverse effect on iron status, compared to an energyrestricted diet alone.